Knowledge leaks in data-driven business models? Exploring different types of knowledge risks and protection measures - Michael Fruhwirth; Viktoria Pammer-Schindler; Stefan Thalmann (Schmalenbach Journal of Business Research (SBUR), 2024)
Data-driven business models imply the inter-organisational exchange of data or similar value objects. Data science methods enable organisations to discover patterns and eventually knowledge from data. Further, by training machine learning models, knowledge is materialised in those models. Thus, organisations might risk the exposure of competitive knowledge by sharing data-related value objects, such as data, models or predictions. Although knowledge risks have been studied in traditional business models, little research has been conducted in the direction of data-driven business models. In this explorative qualitative study, we conducted 28~expert interviews in three rounds (two exploratory and one evaluatory) and identified five types of risks along the three basic types of value objects: data, models and predictions. These risks depend on the context, i.e., when competitive knowledge could be discovered from shared value objects. We found that those risks can be mitigated by technology, contractual regulations, trusted relationships, and adjusting the business model design. In this study, we show that the risk of knowledge leakage is a~relevant risk factor in data-driven business models. Overall, knowledge risks should be considered already during business model design, and their management requires an interdisciplinary approach via a~balanced assessment. The level of knowledge protection from a~technology perspective highly depends on computer science innovations and thus is a~moving target. As an outlook, we suggest that knowledge risk will become even more relevant with the extensive usage of machine learning and artificial intelligence in data-driven business models.
Keywords: 650; Business model innovation; Data analytics; Data-driven business models; Knowledge risks; Risk management; Value objects